Analysis of Teachers' Obstacles in Implementing Literacy Learning in Inclusive Elementary Schools - Utami, Kurnia Dwi; Dina Pratiwi Dwi Santi (Journal of Practice Learning and Educational Development, 2025)
Teachers face many challenges in implementing literacy learning in inclusive schools. The purpose of this research is to analyze the obstacles teachers encounter when applying literacy learning in inclusive schools. This study uses a qualitative approach with a descriptive type. The data collection techniques employed in this research include observation and questionnaires. The research subjects were six classroom teachers at SDN Samadikun. The results show that teachers still face numerous challenges in implementing literacy learning in inclusive schools, ranging from planning, implementation, evaluation, internal factors, and external factors of the teachers themselves. This research can serve as a reference to identify the obstacles that may arise when implementing literacy learning in inclusive schools.